Modelo experimental de endometrite em vacas inoculadas com Escherichia coli inativada por meio de infusão uterina - T.M. Martins; R.L. Santos; T.A. Paixão; J.P.S. Mol; C.S. Muniz; Á.M. Borges (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2016)
The aim of this study was to evaluate the endometrial inflammatory response of nine Zebu cows inoculated through uterine infusion with 30 mL of inactivated Escherichia coli suspension (1 x 109 UFC/mL) and nine with 30 mL of sterile phosphate buffered saline. Endometrial biopsies were performed before and after the inoculations during estrus, and ten days later in the diestrus phase. Neutrophilic infiltrates were observed in 88.8% of samples from the E. coli group in estrus phase and demonstrated different degrees of endometrial inflammation. This study characterizes a suitable model for studying endometritis in cattle.